2007
DOI: 10.1136/pgmj.2006.051805
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of syndrome Z (the interaction of obstructive sleep apnoea with the metabolic syndrome) in a teaching hospital in Singapore

Abstract: Background: Syndrome Z describes the interaction of obstructive sleep apnoea (OSA) with the metabolic syndrome. Purpose of study: A pilot study to determine the prevalence of syndrome Z in a teaching hospital in Singapore. Methods: Patients (age >18 years) recruited for this prospective study had to satisfy three of the following five inclusion criteria: fasting glucose .6.1 mmol/l, blood pressure >130/85 mm Hg, HDL cholesterol ,1.04 mmol/l in men and ,1.2 mmol/l in women, triglycerides >1.7 mmol/l, and a wais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…We found a 60.5% prevalence of OSA in MetS, even using conservative diagnostic OSA criteria (AHI ≥15 events per hour of sleep). The prevalence of OSA observed in this study is in line with two previous reports from different groups (ranging from 68 to 87.5%) that evaluated patients with MetS [17], [18]. Consistently with our data, a recent report found a high prevalence of OSA (∼86%) in obese patients with type 2 diabetes [31].…”
Section: Discussionsupporting
confidence: 93%
“…We found a 60.5% prevalence of OSA in MetS, even using conservative diagnostic OSA criteria (AHI ≥15 events per hour of sleep). The prevalence of OSA observed in this study is in line with two previous reports from different groups (ranging from 68 to 87.5%) that evaluated patients with MetS [17], [18]. Consistently with our data, a recent report found a high prevalence of OSA (∼86%) in obese patients with type 2 diabetes [31].…”
Section: Discussionsupporting
confidence: 93%
“…A high prevalence of MS among male patients with diagnosed OSA referred to sleep laboratories has been reported 12,13 . A recent pilot study 22 found a prevalence of 96% of OSA in 24 patients with MS when adopting a cutoff of ≥5 events/h. However, it was not clear whether the patients were recruited in a consecutive manner.…”
Section: Discussionmentioning
confidence: 99%
“…Los pacientes con SAHS presentan una gran prevalencia de síndrome metabólico 21---23 , así como los pacientes con SAHS e hipertensión arterial 16,24 , únicamente un pequeño porcentaje de casos de pacientes con SAHS deben su etiología a anomalías de tipo anató-mico cráneo-facial. A su vez se ha publicado que hasta un 95% de pacientes con síndrome metabólico pueden presentan SAHS 25 . Por lo tanto, dado que es un síndrome de fácil diagnóstico a partir de las exploraciones complementarias básicas en Atención Primaria, debería ser obligatorio el cribado de SAHS a todo paciente hipertenso que además cumpliera criterios de síndrome metabólico 11 .…”
Section: Discussionunclassified